PENGARUH PENETAPAN HARGA, KUALITAS DAN LOKASI TERHADAP MINAT BELI MAHASISWA DI KIOS BUKU PASAR PALASARI KOTA BANDUNG - Mira Ismirani Ahmar Fudsyi; Dedi Karmana; Dadad Zainal Musadad (Unitri Press, 2020)
This research is important because it aims to gathered information about the effect of price, quality and location on students’ buying interest at the Palasasi market in Bandung. Using quantitative method with infinite population, and using nonprobability sampling, which is accidental sampling. The data is taken from questionnaires filled out by consumers that met by chance. The analysis using multiple regression with SPSS statistics 17.0. The results of the analysis obtained buying interest as the dependent variable -0.752, the independent variable price 0.273, product quality 0.230, location 0.401 is positive. There is a significant influence in the price, production quality and location variables on buying interest in the Palasari Bandung book kiosk. Suggestion is that kiosk owners need to pay attention to consumer attitudes,provision of discounted price, placement of parking location in order to increase revenue.